Al2O3/CuI/PANI nanocomposite catalyzed green synthesis of biologically active 2-substituted benzimidazole derivatives. Issue 22 (14th May 2021) - Kohli, Sahil; Rathee, Garima; Hooda, Sunita; Chandra, Ramesh
Abstract : The fabricated material Al2 O3 /CuI/PANI facilitates the synthesis of 2-substitued benzimidazoles. Abstract : This work is generally focused on the synthesis of an efficient, reusable and novel heterogeneous Al2 O3 /CuI/PANI nanocatalyst, which has been well synthesized by a simple self-assembly approach where aniline is oxidized into PANI and aniline in the presence of KI also acts as a reductant. The nanocatalyst was well characterized by XRD, FTIR, SEM, EDX, TEM, BET and XPS techniques. In this study, the fabricated material was employed for the catalytic one-pot synthesis of 2-substituted benzimidazoles via condensation between o -phenylenediamine and aldehydes in ethanol as a green solvent. The present method is facile and offers several advantages such as high % yield, less reaction time, and no use of additive/bases. Also, the catalyst showed better values of green metrics including low E-factor: 0.17, high reaction mass efficiency: 85.34%, high carbon efficiency: 94%, and high process mass intensity: 1.17.